PARTISIPASI MASYARAKAT DALAM MUSYAWARAH RENCANA PEMBANGUNAN DI KELURAHAN KANYUARA KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Mustanir, Ahmad (JPP (Jurnal Politik Profetik), 2017)
The long term objective of this research is to observe community participation in the development planning meeting (musrembang). Moreover this research is also aimed at understanding socio-cultural factors such as norms, believes, knowledge, behaviors, marital status, age, sex and symbols, which influence community participation in the development planning meeting of the Village of Kanyuara, Sub-district of Watang Sidenreng, District of Sidenreng Rappang. Understanding this objective will provide academic advantages which include inputs of the development of knowledge, particularly on understanding community participation in the development planning meeting. Another advantage is for the researcher to delve into a vast knowledge on influential socio-cultural factors during the development planning meeting in the Village of Kanyara. This research found that community shows their less participation during the musrembang, while at the same time, the above mentioned socio-cultural factors may be categorized influential and even mostly influential towards community participation.